P38 Repeatability of structured light plethysmography (slp) for measurement of respiratory rate in normal subjects. (15th November 2016) - Iles, R; Boer, W De; Khalid, A; Fakhr, S Motamedi; Wilson, R
Abstract : Introduction: Structured Light Plethysmography (SLP) captures movements of a light grid projected onto the thoraco-abdominal (TA) wall to produce a waveform from which a primary derived output is Respiratory Rate (RR). Assessment of repeatability is essential for clinical use, however, physiological variability can confound results. RR agrees within ± 2 breaths per minute (brpm) 1 with Respiratory Inductance Plethysmography (RIP) measured simultaneously on one occasion. We propose that if measurements are repeatable, there would be no difference in agreement between devices over a series of sessions. Aim: This study assessed repeatability of the agreement between SLP and RIP. Methods: 14 subjects (7 male, 7 female) with no respiratory diagnosis underwent 5 minutes of simultaneous measurement with SLP and RIP during quiet breathing. This was repeated on 3 occasions over 2 days, by the same operator, at the same location and using the same devices. RR were calculated for thorax ( THRR), abdomen (ABRR) and the entire thoraco-abdominal (TARR) signals for both devices. Agreement between the two devices was assessed using Bland-Altman plots with LOA set at < ± 2 breaths/min. Results: For TARR and THRR, all points were within 2 SD of the mean; for ABRR, 1 of 14 points was outside of 2 SD, but the LOA were within < ± 2 breaths/min. The mean differences between the two devices were 0.476, 0.605 and 0.524 breaths/min for TARR, THRR and ABRR, respectively. Conclusion: Agreement was observed between the two devices for each set of repeated measurements. We conclude that measurement of RR are repeatable. Reference: Iles R, et al . American Thoracic Society Meeting 2014, A2935.